FAKTOR YANG MEMPENGARUHI PERTUMBUHAN EKONOMI SUMATERA UTARA - Elly Suharyadi (Quantitative Economics Journal, 2014)
The results from the fixed effects model analysis show that the natural resources,gross fixed capital formation, and technology have a significant and positive effectsimultaneously on economic growth in North Sumatra. While labor has a nonsignificant effect on economic growth in North Sumatra. Effect of natural resources, gross fixed capital formation, and technology on economic growth is inelastic and shows a diminishing return for the all the sources of growth. The largest source of economic growth that affects economic growth in North Sumatra is gross fixed capital formation by 0.497 and the largest increase in economic growth due to changes in the sources of economic growth is Pematangsiantar by 5,235 percent, while the smallest is Tanjungbalai City by 2,234 percent.